Targeting Regulated Cell Death with Pharmacological Small Molecules: An Update on Autophagy-Dependent Cell Death, Ferroptosis, and Necroptosis in Cancer - Wu, Junhao; Ye, Jing; Xie, Qiang; Liu, Bo; Liu, Ming (Journal of medicinal chemistry, 2022)
Regulated cell death is a widely attractive subject among the topics of cancer therapy and has gained some advances for discovery of targeted anticancer drugs. In the past decade, nonapoptotic regulated cell death has been implicated in the development and therapeutic responses of a variety of human cancers. Hitherto, targeting autophagy-dependent cell death (ADCD), ferroptosis, and necroptosis with small molecules has been emerging as a hopeful strategy for the improvement of potential cancer therapy, which may have an advantage to bypass the apoptosis-resistance machinery. Thus, in this perspective, we concentrate on the key molecular insights into ADCD, ferroptosis, and necroptosis and summarize the corresponding small molecules in potential cancer therapy. Moreover, the relationships between the three subroutines and small molecules modulating the crosstalk are discussed. We believe that these inspiring findings would be advantageous to exploiting more potential targets and pharmacological small molecules in future cancer treatment.